2018
DOI: 10.3926/jotse.267
|View full text |Cite
|
Sign up to set email alerts
|

E-learning content design standards based on interactive digital concepts maps in light of meaningful learning theory and constructivist learning theory

Abstract: The present study aims to identify standards of interactive digital concepts maps design and their measurement indicators as a tool to develop, organize and administer e-learning content in the light of Meaningful Learning Theory and Constructivist Learning Theory. To achieve the objective of the research, the author prepared a list of E-learning content design standards based on interactive digital concepts maps. It involved (11) general standards and (40) performance indicators. It was investigated by 21 tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
10
0
4
Order By: Relevance
“…Asiksoy and Ozdamli (2017) in their study on education technologies for constructivist learning found that the most frequently used tool was the computer and the most common platform was learning management system. Additionally, Afify (2018) found digital concept mapping an effective tool in support of constructivist learning theory. Scott (2015) believes the current educational system with fixed curriculum and delivery method obscures personalised learning and suggests the need to adopt personalised learning for 21st century education.…”
Section: St Centurymentioning
confidence: 96%
See 1 more Smart Citation
“…Asiksoy and Ozdamli (2017) in their study on education technologies for constructivist learning found that the most frequently used tool was the computer and the most common platform was learning management system. Additionally, Afify (2018) found digital concept mapping an effective tool in support of constructivist learning theory. Scott (2015) believes the current educational system with fixed curriculum and delivery method obscures personalised learning and suggests the need to adopt personalised learning for 21st century education.…”
Section: St Centurymentioning
confidence: 96%
“…Yet another pedagogy that has been explored in higher education is constructivist learning which emerges from the concepts developed by pioneers, Piaget and Vygotsky. Constructivist learning allows for students to actively construct their own knowledge in order for learning to be meaningful and effective (Afify, 2018;Alt, 2017;Asiksoy & Ozdamli, 2017;Noel, 2015;Scott, 2015). Noel (2015) suggested use of blogs in education to create a constructivist learning environment that supports knowledge development through student engagement, reflection and collaboration.…”
Section: St Centurymentioning
confidence: 99%
“…Além disso, mapas conceituais fornecem uma interface flexível de acesso ao conteúdo e facilitam o acesso ao conteúdo digital sem esgotar a memória operacional do aluno (Afify, 2018, p. 5 e 6, tradução nossa) Segundo Novak (1998 apud Afify, 2018), o desenvolvimento de mapas conceituais para o design e a produção de conteúdos também baseia-se em uma perspectiva construtivista, já que a ideia é permitir que os alunos organizem e reformulem o conhecimento por conta própria e os representem a partir das atividades propostas, sem a ajuda do professor.…”
Section: Design De Conteúdounclassified
“…The amount of digital content for e-learning has grown significantly over the past decade. The availability and growth of digital information create the need for tools that help students and teachers effectively organize and integrate electronic resources and seek information necessary to achieve the learning goals (Afify, 2018). One of the greatest scientific challenges of the 21st century is how to master, organize and extract useful knowledge from the overwhelming flow of information made available by today's data collection systems and computing resources (Olcott, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Information visualization performs several important educational functions at once. Visual information is more quickly perceived and assimilated in the learning process, which is associated with the peculiarities of the neurophysiological activity of the brain (Afify, 2018;Ferreira et al, 2019). Visualization allows one to transfer data in a more visual and compact form, accommodating more information in the same visual space and at the same time guaranteeing the speed and efficiency of its perception (Liu et al, 2020;Toetenel & Rienties, 2016).…”
Section: Introductionmentioning
confidence: 99%